Catastrophic Health Expenditure After the Implementation of Health Sector Evolution Plan: A Case Study in the West of Iran - Bakhtiar Piroozi; Ghobad Moradi; Bijan Nouri; Amjad Mohamadi Bolbanabad; Hossein Safari (Kerman University of Medical Sciences, 2016)
Background: One of the main objectives of health systems is the financial protection against out-of-pocket (OOP) health expenditures. OOP health expenditures can lead to catastrophic payments, impoverishment or poverty among households. In Iran, health sector evolution plan (HSEP) has been implemented since 2014 in order to achieve universal health coverage and reduce the OOP health expenditures as a percentage of total health expenditures. This study aimed to explore the percentage of households facing catastrophic health expenditures (CHE) after the implementation of HSEP and the factors that determine CHE. Methods: A total of 663 households were selected through a cluster sampling based on the census framework of Sanandaj Health Center in July 2015. Data were gathered using face-to-face interviews based on the household section of the World Health Survey questionnaire. In this study, according to the World Health Organization (WHO) definition, if household health expenditures were equal to or more than 40% of the household capacity to pay, household was considered to be facing CHE. The determinants of CHE were analyzed using logistic regression model. Results: The rates of households facing CHE were 4.8%. The key determinants of CHE were household economic status, presence of elderly or disabled members in the household and utilization of inpatient or rehabilitation services. Conclusion: The comparison of our findings and those of other studies carried out using a methodology comparable with ours in different parts of Iran before the implementation of HSEP suggests that the implementation of recent reforms has reduced CHE at the household level. Utilization of inpatient and rehabilitation services, the presence of elderly or disabled members in the household and the low economic status of the household would increase the likelihood of facing CHE. These variables should be considered by health policy-makers in order to review and revise content of recent reform, thus financially protecting public against CHE.